2013
DOI: 10.1080/02640414.2013.781664
|View full text |Cite
|
Sign up to set email alerts
|

Protocol variations in arm position influence the magnitude of waist girth

Abstract: Waist girth is recognised as a better predictor of obesity, particularly abdominal obesity, compared to other measures. Although several protocols for waist girth exist, arm position is either ignored, or not specified in unambiguous terms. Therefore, the purpose of this study was to determine if arm position influenced anthropometric waist girth measurement. Waist girth was measured in 92 adults (19 males, 73 females) with arms relaxed, abducted, horizontal, folded across the chest (three variations) and rais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Further, participants might tend to hold their breath and pull in their stomach due to the contact during MM, either reflexively or consciously. Additionally, studies demonstrate that the arm posture can significantly influence the WC [ 9 , 29 ]. During AM in our study, the arm position was fixed so that it neither shadows the torso nor stretches the waist area.…”
Section: Discussionmentioning
confidence: 99%
“…Further, participants might tend to hold their breath and pull in their stomach due to the contact during MM, either reflexively or consciously. Additionally, studies demonstrate that the arm posture can significantly influence the WC [ 9 , 29 ]. During AM in our study, the arm position was fixed so that it neither shadows the torso nor stretches the waist area.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this difference is that volunteers tend to pull their stomach in for manual measurements (Jaeschke, Steinbrecher & Pischon, 2015). Other studies showed that arm posture had a significant influence on WC measurements (Lennie et al, 2013; Lu, Wang & Mollard, 2010). In our study arm posture was different in the scanner (slightly bent elbows and slightly separated from the body, but not too far away in order not to leave the measuring area) as in manual WC, where volunteers had to hold their arms further away from the trunk due to the measurement procedure.…”
Section: Discussionmentioning
confidence: 93%
“…A possible explanation for this difference is that volunteers tend to pull their stomach in for manual measurements (Jaeschke et al 2015). Other studies showed that arm posture had a significant influence on WC measurements (Lennie et al 2013;Lu et al 2010). In our study arm posture was different in the scanner (slightly bend elbows and slightly separated from the body, but not too far away in order not to leave the measuring area) as in manual WC, where volunteers had to hold their arms further away from the trunk due to the measurement PeerJ reviewing PDF | (2019:06:38312:1:1:NEW 22 Oct 2019)…”
Section: Discussionmentioning
confidence: 99%